New Standards for the Exercise of the Public Function of Urban Territorial Planning: Analysis of Article 28 decies of the General Law of Urbanism and Constructions. (Justicia &Derecho, 2020)
Urban territorial planning and its instruments have undergone several reforms recently. The increase in citizen participation, the incorporation of the objective image and the inclusion of minimum standards in the creation of these instruments, are just some of the modifications introduced by the legislation in order to contribute to the transparency of the land market. In this context, this article focuses on the analysis of Article 28 decies of the General Law of Urban Planning and Construction, which is the cornerstone of the new way of planning territorially in Chile. This paper deals in detail with each new standard, based on recent legislation and the current National Urban Development Policy.
Keywords: motivation; territorial cohesion